Risiko ergonomi pada penjahit di wilayah pesisir - Panggeleng, Andi Mifta Farid; Maharja, Rizky (Holistik Jurnal Kesehatan, 2025)
Background: Tailors are one of the professions that are highly vulnerable to health problems, particularly musculoskeletal disorders (MSDs). MSDs among tailors are caused by several factors, such as repetitive work, static working postures, and non-ergonomic work environments. This issue highlights the urgency of conducting a more in-depth study on ergonomic risk factors among tailors. Purpose: To identify ergonomic risk factors among tailors in coastal areas. Method: This quantitative study employed a cross-sectional design and was conducted in East Banggae District. The study population consisted of all tailors working in the East Banggae area. Samples were selected using purposive sampling techniques. Data were collected through questionnaires, observations, measurements, and interviews. The statistical analysis used was the Chi-square test. Results: The variables of age (p-value = 0.042), working hours (p-value = 0.016), work fatigue (p-value = 0.016), physical workload (p-value = 0.000), mental workload (p-value = 0.000), and working posture (p-value = 0.000) were significantly associated with MSD complaints among tailors. Meanwhile, length of employment (p-value = 0.828) was not associated with MSD complaints. Conclusion: The majority of tailors experienced mild MSD complaints. Furthermore, MSD complaints among tailors in coastal areas were influenced by age, working hours, work fatigue, physical workload, mental workload, and working posture. In contrast, length of employment did not affect MSD complaints among tailors.   Keywords: Coastal Areas; Ergonomics; Musculoskeletal Disorders (MSDs) Complaints; Tailors.   Pendahuluan: Pekerja penjahit merupakan salah satu profesi yang sangat rentan mengalami masalah kesehatan seperti gangguan otot atau Musculuskeletal Disorders (MSDs). MSDs terjadi pada penjahit disebabkan oleh sejumlah faktor seperti pekerjaan berulang, posisi kerja statis dan lingkungan kerja yang tidak ergonomis. Masalah ini tentunya menjadi salah satu urgensi mengapa kajian lebih mendalam mengenai studi risiko ergonomi penjahit perlu dilakukan Tujuan: Untuk mengidentifikasi faktor risiko ergonomi pada penjahit di wilayah pesisir. Metode: Penelitian kuantitatif dengan desain cross-sectional yang akan dilaksanakan di Kecamatan Banggae Timur. Populasi pada penelitian ini adalah seluruh penjahit yang tersebar di wilayah Banggae Timur. Adapun metode pemilihan sampel memakai teknik purposive sampling. Pengumpulan data menggunakan kuesioner, observasi, pengukuran, wawancara dan uji statistik yang digunakan adalah Chi-square. Hasil: Variabel usia (p-value= 0.042), lama kerja (p-value =0.016), kelelalahan kerja (p-value =0.016), beban kerja fisik (p-value = 0.000), beban kerja mental (p-value =0.000) dan postur tubuh (p-value =0.000) memiliki hubungan dengan keluhan MSDs penjahit, sedangkan variabel masa kerja (p-value =0.828) tidak berhubungan dengan keluhan MSDS. Simpulan: Mayoritas penjahit mengalami keluhan MSDs tingkat ringan. Selain itu, keluhan MSDs yang dialami oleh penjahit di wilayah pesisir ini dipengaruhi oleh usia, lama kerja, kelelahan kerja, beban kerja fisik, beban kerja mental, dan postur tubuh. Sementara itu, masa kerja tidak memengaruhi keluhan MSDs penjahit.   Kata Kunci: Ergonomi; Keluhan Musculuskeletal Disorders (MSDs); Penjahit; Wilayah Pesisir.